Cortical Auditory Evoked Potentials with Simple (Tone Burst) and Complex (Speech) Stimuli in Children with Cochlear Implant - Martins,Kelly Vasconcelos Chaves (2017)
Abstract Introduction The registry of the component P1 of the cortical auditory evoked potential has been widely used to analyze the behavior of auditory pathways in response to cochlear implant stimulation. Objective To determine the influence of aural rehabilitation in the parameters of latency and amplitude of the P1 cortical auditory evoked potential component elicited by simple auditory stimuli (tone burst) and complex stimuli (speech) in children with cochlear implants. Method The study included six individuals of both genders aged 5 to 10 years old who have been cochlear implant users for at least 12 months, and who attended auditory rehabilitation with an aural rehabilitation therapy approach. Participants were submitted to research of the cortical auditory evoked potential at the beginning of the study and after 3 months of aural rehabilitation. To elicit the responses, simple stimuli (tone burst) and complex stimuli (speech) were used and presented in free field at 70 dB HL. The results were statistically analyzed, and both evaluations were compared. Results There was no significant difference between the type of eliciting stimulus of the cortical auditory evoked potential for the latency and the amplitude of P1. There was a statistically significant difference in the P1 latency between the evaluations for both stimuli, with reduction of the latency in the second evaluation after 3 months of auditory rehabilitation. There was no statistically significant difference regarding the amplitude of P1 under the two types of stimuli or in the two evaluations. Conclusion A decrease in latency of the P1 component elicited by both simple and complex stimuli was observed within a three-month interval in children with cochlear implant undergoing aural rehabilitation.